Correlation between Severity of Coronary Artery Stenosis and Perfusion Defect Assessed by SPECT Myocardial Perfusion Imaging (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):608-13The abstract of this article is available on the PubMed website